(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In conclusion, architecture and everything around us and events have something to do with nature. The harmonization of architecture with nature, on the other hand, reflects the pros and cons of buildings. Man has long intelligently and intuitively addressed the living nature in his architectural and construction activities, and nature has helped solve his various problems. The term "bionics" comes from the Greek word bios, which means "life." The word "nica" is derived from electronics and has opened up a direction in science as a new term. The main content of the article is to provide information on what bionics means for the origin and application of this science nowadays.